The Effect of Storage and Time of Blood Specimen Examination of Plasma Prothrombin Time and Activated Partial Thromboplastin Time Stabilities - Aditea Etnawati Putri1 , Yulia Nadar Indrasari2 , Yetti Hernaningsih2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
his was an analytical study with cross sectional design. Collection of blood specimens was carried out by consecutive sampling during March-June 2019. Blood specimens in this study were healthy adults aged ?21 years who underwent general medical check-up or blood donors who met the inclusion criteria and signed informed consent. A total of 71 samples were stored at room temperature and temperature 4-8 °C, then PT (prothrombin time) and aPTT (activated partial thromboplastin time) checks were carried out at 0, 4, 12, and 24 hours. Data were analyzed by using Kolmogorov-Smirnov Test, paired t test and Wilcoxon Signed Rank Test. There were differences in the results of PT in the room temperature specimens and 4-8 °C at 4 hours, 12 hours, and 24 hours with p value <0.001. This was also found in the aPTT parameter, but for specimens at 4-8 °C at the 24th hour examination the results of changes in aPTT were not statistically significant with p values 0.062. Different PT and aPTT tests at the two storage areas and at different examination times obtained different and statistically significant results with p value <0.001. Examination of hemostasis physiology requires special attention, where pre-analytic plays an important role which can influence the overall test results. The aspects of time and storage on the stability of PT and aPTT specimens are illustrated in this study where significant differences were obtained with p values <0.001. Examination and storage of coagulation study specimens in accordance with CLSI recommendations will provide accurate results and accurately describe the state of the specimen according to the patient’s clinical condition.